2013
DOI: 10.3748/wjg.v19.i23.3642
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track surgery could improve postoperative recovery in radical total gastrectomy patients

Abstract: FTS could be safely applied in radical total gastrectomy to accelerate clinical recovery of gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 35 publications
5
101
1
6
Order By: Relevance
“…In this review, studies investigating the cost as either a primary or secondary outcome have been conducted in Europe, [7][8][9][10][11][12] Asia, [13][14][15][16][17][18] North America, 2,19 USA, 20 and Australasia. 1,21 Six of the 17 studies were systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, studies investigating the cost as either a primary or secondary outcome have been conducted in Europe, [7][8][9][10][11][12] Asia, [13][14][15][16][17][18] North America, 2,19 USA, 20 and Australasia. 1,21 Six of the 17 studies were systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred nineteen patients were randomized to either an ERAS group (n = 59) or a conventional care group (n = 60). 16 Investigators reported significant reductions in time to flatus and defecation, pain scores, complications, and costs (P \ 0.05).…”
Section: Gastric Surgerymentioning
confidence: 99%
“…There were 11 articles (1,128 patients) on fast track oesophageal surgery [11][12][13][14][15][16][17][18][19][20][21] and 7 (329 patients) on fast track gastric surgery. 12,[22][23][24][25][26][27] Ten articles were case series, five were case-controlled studies and three were RCTs (all gastrectomy related with a Jadad score of 1 or 2). All articles involved single centre data, most being small volume.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of included studies is generally poor, many are retrospective and there were only three RCTs, all single centre 22,23,25 with only one blinded. 22 The maximum number per arm in any of the studies was 61 patients and all excluded those undergoing neoadjuvant chemo or radiotherapy. Restricting our review to the English language literature may have led to the omission of some studies but this is unlikely to have influenced our summary outcome estimates.…”
Section: Limitationsmentioning
confidence: 99%
“…Although some reports have described the use of the ERAS protocol for patients undergoing surgery for gastric cancer, clear and convincing evidence for the usefulness of this protocol for such patients has not been established [15][16][17][18][19][20][21][22]. Consensus guidelines for enhanced recovery after gastrectomy have been published [23].…”
Section: Introductionmentioning
confidence: 99%